Women's bodies, rebirth, and Shin Buddhism: Insights and challenges for Christianity. Issue 3 (17th July 2019) - Largen, Kristin Johnston
Abstract: In this article, I examine a traditional Shin teaching on women and women's bodies as they relate to rebirth in Amida's Pure Land and ask how that teaching might inform Christian doctrines on women's bodies. After an analysis of the role of women's bodies in the broader Shin teachings around Amida's compassion and rebirth in the Pure Land, I conclude by raising questions for Christianity this analysis invites and suggest further lines of inquiry that might help open up more positive understanding of women and women's bodies in contemporary Christianity.